2014
DOI: 10.5551/jat.24372
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TLR4 in Oxidized LDL/β2GPI/Anti-β2GPI-Induced Transformation of Macrophages to Foam Cells

Abstract: Aim: It has been reported that oxidized low-density lipoprotein (oxLDL) forms a stable and non-dissociable complex with β2-glycoprotein I (β2GPI) and that IgG anti-β2GPI autoantibodies are able to recognize this complex, thus facilitating macrophage-derived foam cell formation in patients with antiphospholipid syndrome (APS). However, the immunopathological mechanisms of oxLDL/β2GPI complexes in promoting foam cell formation are not fully understood. In this study, we examined the role of toll-like receptor 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 49 publications
1
36
0
1
Order By: Relevance
“…Recent studies have suggested that EGFR can also be activated without the typical ligands29, and it can function in intracellular membranes30. Toll-like receptor 4 (TLR4) has been reported to be directly activated by ox-LDL and mediate pathological pathways and phenotypes313233. In addition, expression of TLR4-induced genes in lipopolysaccharide-stimulated myeloid cells requires EGFR kinase activity18.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that EGFR can also be activated without the typical ligands29, and it can function in intracellular membranes30. Toll-like receptor 4 (TLR4) has been reported to be directly activated by ox-LDL and mediate pathological pathways and phenotypes313233. In addition, expression of TLR4-induced genes in lipopolysaccharide-stimulated myeloid cells requires EGFR kinase activity18.…”
Section: Resultsmentioning
confidence: 99%
“…The main role of the aβ2GPI antibodies, especially those specifically targeting domain I [20], is widely accepted and present results seem to further confirm their importance with regard to CV risk stratification, since PAF-AH appeared particularly elevated in aβ2GPI-positive patients and more so in those displaying LAC activity and carrying the IgG isotype. This particular association may be explained by the fact that IgG aβ2GPI antibodies are able to recognize the stable complex between oxLDL and β2GPI, thus facilitating macrophage-derived foam cell formation in patients with APS [15]. The immune-pathological mechanisms sustained by oxLDL/β2GPI complexes are not yet fully understood, but Toll-like receptor 4 (TLR4) was recently shown to be involved [15].…”
Section: Discussionmentioning
confidence: 99%
“…This particular association may be explained by the fact that IgG aβ2GPI antibodies are able to recognize the stable complex between oxLDL and β2GPI, thus facilitating macrophage-derived foam cell formation in patients with APS [15]. The immune-pathological mechanisms sustained by oxLDL/β2GPI complexes are not yet fully understood, but Toll-like receptor 4 (TLR4) was recently shown to be involved [15]. TLR4 could be the key player linking PAF-AH up-regulation to aβ2GPI IgG antibodies in APS, as evidenced by a mouse model of preterm delivery which demonstrated that PAF effects and signalling depend upon TLR4 stimulation [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the IRAK1/4 inhibitor reduced the production of IL-1 and TNF-while also decreasing TLR4 expression and NF B activation. Furthermore, the expression of TLR4 and activation of NF-B played an important role during the transformation of macrophages to foam cells, which may accelerate the development of atherosclerosis 35) . TLR4 signaling was the mediator of chronic inflammation and an important regulator of atherogenesis 36) .…”
Section: Acknowledgmentsmentioning
confidence: 99%